Gender, Ras, Dan Kelas Dalam Novel The Adventures Of Huckleberry Finn Karya Mark Twain - Salman Hasyim A; Salwa Khuzaimatu S; Tsulis Khoerunnisa; Nurholis Nurholis (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study applies a qualitative research method with an intersectionality approach to analyze Mark Twain's The Adventures of Huckleberry Finn, which explores issues related to race, gender, and class in the context of post-civil war America. The main focus of this research is how racial, gender, and class identities interact with each other in shaping the experiences of the characters, specifically Huck, a white boy from the lower class, and Jim, an escaped African-American slave. Through the analysis of their cross-racial relationship, this study highlights the complex power dynamics, where Jim is trapped in a racial and class hierarchy, while Huck struggles against social pressure from female authority figures representing patriarchy. The findings of this study suggest that character identities are shaped by the intersection of multiple factors, providing a deeper understanding of the challenges faced in maintaining or resisting oppressive systems of power. The Adventures of Huckleberry Finn, a classic novel by Mark Twain, is a clear example of how literary works that criticize racial injustice can be misinterpreted and censored. Twain presents a scathing satire of American society, exposing its hypocrisy and failure to realize the promised values of equality. As such, the deep meanings contained within are buried under layers of superficial and biased interpretations.